A New Method for Centrality Measurement Using Generalized Fuzzy Graphs - R. Dhanalakshmi; Junaid Rashid; Jungeun Kim; Arun Kumar Sivaraman; Usman Naseem; Rajiv Vincent (Discrete Dynamics in Nature and Society)
The fuzzy graph is the foundation of many actual structures such as networking, picture planning, and so on. Generalized fuzzy graphs (GFG) are ideal for avoiding certain constraints of fuzzy graphs. Social networks are a useful and powerful way to link citizens worldwide. A central person in a social network is to deny the leading people in it. Different centrality steps have also been established over the years. We evaluated the centrality of the social network through a general fuzzy graph in this article. An application to detect the central person in any online group like WhatsApp is described in this study by using generalized fuzzy graphs. Also, a few important results are established in this study.